2015
DOI: 10.3892/ol.2015.3628
|View full text |Cite
|
Sign up to set email alerts
|

Levels of plasma Epstein-Barr virus DNA prior and subsequent to treatment predicts the prognosis of nasopharyngeal carcinoma

Abstract: Abstract. The level of Epstein-Barr virus DNA (EBV-DNA) in the plasma prior and subsequent to treatment is a reliable biomarker for the screening, diagnosis, monitoring and prognosis of nasopharyngeal carcinoma (NPC). The present retrospective study aimed to determine whether pre-and post-treatment levels of plasma EBV-DNA were predictive of survival in a large sample of patients with NPC. The level of plasma EBV-DNA in 637 NPC patients prior and subsequent to treatment was determined by quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 24 publications
7
24
1
10
Order By: Relevance
“…Multiple reports have shown that pre-and post-treatment plasma EBV DNA are prognostic factors for NPC progression and survival [5,[14][15][16][17][18], and these ndings are also con rmed in this study. However, these previous studies mainly focused on few time points, for example, pre-treatment and 3 months posttreatment [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Multiple reports have shown that pre-and post-treatment plasma EBV DNA are prognostic factors for NPC progression and survival [5,[14][15][16][17][18], and these ndings are also con rmed in this study. However, these previous studies mainly focused on few time points, for example, pre-treatment and 3 months posttreatment [19].…”
Section: Discussionsupporting
confidence: 83%
“…Cell-free EBV DNA from NPC tumor cells can be detected in the plasma of NPC patients [5], and the plasma DNA load can re ect the tumor load and residual disease or subclinical metastases [6]. Therefore, EBV DNA is widely considered as a reliable biomarker for early screening, clinical staging, prognosis prediction, individualized treatment and follow-up monitoring in NPC [7][8][9][10][11][12][13].While multiple studies have reported that plasma EBV DNA could be used as a predictive marker for NPC prognosis [5,[14][15][16][17][18], however, these studies only measured plasma EBV DNA load at limited time points, such as pre-treatment and 3 months post-treatment. We suggested that a long-term monitoring of dynamic changes of plasma EBV DNA could improve its prognostic value in NPC.In a meta-analysis by Qu et al [19], plasma EBV DNA was measured primarily from day 1 to 3 months post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating tumour DNA (ctDNA) from virally induced cancers has previously been shown to be clinically useful as a diagnostic test for other oncovirus-driven cancers such as HBV-induced hepatocellular carcinoma 14 and Epstein-Barr virus (EBV)-induced nasopharyngeal carcinomas (NPC). 15,16 HPV-DNA has also been demonstrated to be present in blood of patients with HPV-induced cervical cancer but absent from patients with pre-cursor cervical lesions. 17,18 The great advantage of a biomarker for oncovirus-driven cancers is the specificity of the biomarker, which sets it apart from the ctDNA biomarkers proposed for use in other solid cancers.…”
Section: Introductionmentioning
confidence: 99%
“…В данном исследовании, которое проводилось в неэндемичном регионе (Россия), мы изучали клиническое значение серологических маркёров ВЭБ, титры IgA/ВКА-и IgG/ВКА-антител, а также показатели концентрации ДНК ВЭБ в плазме больных нРНГ до и после лечения, в состоянии ремиссии или рецидива. Полученные данные в целом согласуются с результатами исследований, проведённых в эндемичных по нРНГ регионах [41,42], где тестирование концентраций ДНК ВЭБ и титров IgA/ ВКА-антител в плазме широко используется в качестве диагностического и прогностического инструмента для определения рецидива и выживаемости больных нРНГ [43][44][45]. В наших исследованиях мы также показали высокую ценность показателей концентрации ДНК ВЭБ и титров антител IgA/ВКА (но не IgG/ВКА) в плазме для диагностики нРНГ и оценки клинического состояния болезни (ремиссии или рецидива).…”
Section: Discussionunclassified